2014
DOI: 10.1016/j.jmps.2013.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic necking in materials with strain induced martensitic transformation

Abstract: Abstract:This work investigates the interplay between inertia and strain induced martensitic transformation (SIMT) on necking inception and energy absorption in dynamically stretched cylindrical rods. For that task a linear stability technique, derived within a quasi-1D framework and specifically accounting for SIMT, has been developed. Likewise, finite element simulations have been performed, using a specific constitutive equation to consider SIMT. Stability analysis and numerical simulations demonstrate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 47 publications
(66 reference statements)
1
39
0
Order By: Relevance
“…Somani et al (2009) and Huang et al (2011) reported that martensite transformation could be enhanced significantly by ultra-fined austenite grains in 301LN stainless steel, which was contrary to the common observations that smaller austenite grains are more stable against transformation (Iwamoto and Tsuta, 2000;Shi et al, 2010b). Other factors, such as strain rate, temperature and stress triaxiality, were also found to have strong influences on TRIP effect: (i) at the low strain rate range (<1/s), TRIP effect happens at earlier strain for higher strain rate, while the maximum volume fraction of martensite decreases with increasing strain rate (Das and Tarafder, 2009;Lee et al, 2014;Prüger et al, 2014;Zaera et al, 2014); (ii) TRIP effect is suppressed with increasing temperature at the low temperature range (77-332 K) (Prüger et al, 2014;Zaera et al, 2014;Lebedev and Kosarchuk, 2000); (iii) increasing stress triaxiality intensifies TRIP effect (Lebedev and Kosarchuk, 2000;Jacques et al, 2007).…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Somani et al (2009) and Huang et al (2011) reported that martensite transformation could be enhanced significantly by ultra-fined austenite grains in 301LN stainless steel, which was contrary to the common observations that smaller austenite grains are more stable against transformation (Iwamoto and Tsuta, 2000;Shi et al, 2010b). Other factors, such as strain rate, temperature and stress triaxiality, were also found to have strong influences on TRIP effect: (i) at the low strain rate range (<1/s), TRIP effect happens at earlier strain for higher strain rate, while the maximum volume fraction of martensite decreases with increasing strain rate (Das and Tarafder, 2009;Lee et al, 2014;Prüger et al, 2014;Zaera et al, 2014); (ii) TRIP effect is suppressed with increasing temperature at the low temperature range (77-332 K) (Prüger et al, 2014;Zaera et al, 2014;Lebedev and Kosarchuk, 2000); (iii) increasing stress triaxiality intensifies TRIP effect (Lebedev and Kosarchuk, 2000;Jacques et al, 2007).…”
Section: Introductionmentioning
confidence: 61%
“…Moreover, most energy absorbers require materials that are (i) capable of keeping a high value of the stress upon dynamic deformation, and (ii) able to show a large value of strain at failure e f . The second requirement is strongly dependent on the onset of strain localization which triggers material failure (Meyer and Manwaring, 1986;Meyers et al, 1994;Subhash et al, 1997;Jia et al, 2003;Wei et al, 2004;Xue et al, 2005;Bronkhorst et al, 2006;Wei et al, 2006a,b;Mishra et al, 2008;Yang et al, 2011;Yuan et al, 2012;Zaera et al, 2014). So the purpose of this paper is to investigate the mechanical properties for the 5Mn TRIP steel with ultra-fined grains (Shi et al, 2010a;Luo et al, 2011;He et al, 2013) under dynamic shear loading at high strain rate.…”
Section: Introductionmentioning
confidence: 99%
“…It is also well known that the observed resistance to plastic deformation is a rate-controlling process and can be affected by the strain rate [23][24][25]27,28]. The quasi-static tensile behaviors and the dynamic behaviors at high strain rates (~10 3 /s) for TRIP steels, TWIP steels, DP steels and HSSS have been well characterized in previous research [1,2,20,[41][42][43][44][45][46][47][48][49][50], while there is very limited experimental data on various steels at the intermediate strain rates (from 1 to 100/s) [51][52][53][54][55], which is an extremely important transition region in application of automobile industry, since vehicle crushing often happens in this strain rate range or within an even higher strain rate range. Thus, the potential applications for the HSSS in the automobile industry require a comprehensive understanding of deformation physics subjected to dynamic loading at intermediate strain rates.…”
Section: Introductionmentioning
confidence: 87%
“…This is a characteristic of multiphase TRIP steels and metastable austenitic grades, that are widely used for energy absorption in crash or blast protection applications [14e18]. It has to be noted that the behavior of solids showing martensitic transformation at high strain rates has been recently analyzed in perforation [19] and dynamic necking [20,21] problems. These works identified loading conditions and characteristics of transformation kinetics for which martensitic transformation delays plastic localization and boosts the energy absorption capacity of the material.…”
Section: Introductionmentioning
confidence: 99%
“…Work hardening materials are defined by a simple Ludwik hardening law, whereas transformation hardening materials are described as in Zaera et al [21]. In Section 3 we shortly recapitulate the analytical investigation of the steady cavitation fields for arbitrary hardening response, with earlier reference to Durban and Fleck [8] and Masri and Durban [10].…”
Section: Introductionmentioning
confidence: 99%